FACTORS AFFECTING ADOPTION OF EMBRYO TRANSFER TECHNOLOGY IN DAIRY CATTLE IN KENYA - Kios, David Kiprotich; Tsuma, Victor; Mutembei, Henry (Advances in Social Sciences Research Journal, 2018)
The use of assisted reproductive technologies in dairy farming has supported many countries to achieve sustainable milk production milk. These technologies include; artificial insemination (AI) using conventional and gender selected semen, embryo transfer based on multiple ovulation & embryo transfer (MOET) or invitro embryo production (IVEP), among others. A study was carried out to determine factors that affect adoption of embryo transfer (ET) in Kenya. A questionnaire was designed and administered to 385 respondents to determine their perception on MOET adoption. None of the respondents had used MOET to improve their livestock. This was mainly attributed to lack of awareness of the existence of the technique as shown by 58.7% of respondents in Uasin Gishu and 46.7% in TransNzoia counties). Other factors affecting adoption included; Lack of experts to carry out the procedure, cost of the technique and non-availability. However, the respondents would adopt MOET if it’s made available (72% in Uasin Gishu and 79% in TransNzoia Counties). More than 60% of respondents in both counties breed their own replacement heifers and only 40% outsource the heifers from other breeders. Sensitization of the farmers on the available assisted reproductive techniques and their potential is the first step towards achievement food and nutrition security as envisioned in the Big Four agenda and Vision 2030 of the government of Kenya and sustainable development goals (SDGs).